2005
DOI: 10.1007/s10634-005-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Formation of the Condensed Phase in Aluminum Combustion in Carbon Dioxide

Abstract: Aluminum powders are widely used in mixed energy-rich materials (rocket propellants, explosives, pyrotechnics) for improving their energy characteristics. Carbon dioxide is a typical component of the oxidizing gas medium in the combustion of aluminum particles in energy-rich materials. The efficiency of using aluminum in energy-rich materials is often decreased because of an increase in the mass fraction of the condensed phase in the combustion products. For example, in metallized rocket propellants, this lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…So the sample weight decreased. The previous energy dispersion X-ray spectrometry also showed the amount of C increased between 600 and 1000 ℃ and then decreased to the minimum at 1200 ℃ [13].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…So the sample weight decreased. The previous energy dispersion X-ray spectrometry also showed the amount of C increased between 600 and 1000 ℃ and then decreased to the minimum at 1200 ℃ [13].…”
Section: Resultsmentioning
confidence: 77%
“…The earlier papers has also reported that other forms of aluminum oxides may formed [9,13], such as Al 4 C 3 , Al 2 OC and Al 4 O 4 C. But this can not explain the weigh loss, because if any of these aluminum oxides decompose into Al, then it can continue to react with CO 2 to formed Al 2 O 3 , then the weight would increase. So the most possibly reason is Al can react with CO to produce C. In low pressure, C can react with CO 2 to produce CO at 800-1200 ℃.…”
Section: Resultsmentioning
confidence: 99%
“…None of the aluminium oxycarbides were detected in the experiment of combustion of aluminium in CO 2 performed by Rossi [35]. Similarly, Assovskii et al [36] have also reported Al 3 C 4 emerging in the temperature range 1800-2300 K, and that any carbon phase is unexpectedly absent when combustion of millimetre-sized aluminium was conducted in a CO 2 atmosphere under 20 MPa. In hot ambient gases, aluminium oxycarbide can be melted, which promotes direct surface reactions.…”
Section: Resultsmentioning
confidence: 89%
“…Sarou-Kanian et al [37] observed Al 3 C 4 in residua, and that aluminium oxycarbide and carbon are intermediate products as surface reactions in the initial reactions stage. The result of the quantitative analysis by Assovskii et al [36] showed the concentration of α-Al 2 O 3 is less than 30%, and the γ -Al 2 O 3 is in larger proportion in the condensed sample. The discrepancy proves that combustion of aluminium is intensive in our experiments.…”
Section: Resultsmentioning
confidence: 99%